2009
DOI: 10.1021/es901146t
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of Peroxy Radicals Using Chemical Amplification−Cavity Ringdown Spectroscopy

Abstract: The peroxy radical chemical amplification (PERCA) method is combined with cavity ringdown spectroscopy(CRDS) to detect peroxy radicals (HO2 and RO2). In PERCA, HO2 and RO2 are first converted to NO2 via reactions with NO, and the OH and RO coproducts are recycled back to HO2 in subsequent reactions with CO and O2; the chain reactions of HO2 are repeated and amplify the level of NO2. The amplified NO2 is then monitored by CRDS, a sensitive absorption technique. The PERCA-CRDS method is calibrated using a HO2 ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 31 publications
(112 reference statements)
1
47
0
Order By: Relevance
“…The NO 2 product is then quantified by the appropriate measurement technique, e.g. luminol chemiluminescence (Parker et al, 2009), laser-induced fluorescence (Sadanaga et al, 2004) and cavity-ring-down (Liu et al, 2009) spectroscopy. In order to obtain absolute concentrations, the chain length of the amplification and the response of the NO 2 detector has to be determined in calibration experiments.…”
Section: Introductionmentioning
confidence: 99%
“…The NO 2 product is then quantified by the appropriate measurement technique, e.g. luminol chemiluminescence (Parker et al, 2009), laser-induced fluorescence (Sadanaga et al, 2004) and cavity-ring-down (Liu et al, 2009) spectroscopy. In order to obtain absolute concentrations, the chain length of the amplification and the response of the NO 2 detector has to be determined in calibration experiments.…”
Section: Introductionmentioning
confidence: 99%
“…The PeRCEAS instrument reported by Liu et al (2009) differs both in scope (airborne measurements for PeRCEAS vs. ground-based measurements) and general layout (pressure stabilized inlet of PeRCEAS vs. Teflon tubing inlet, compact 19 NO 2 detector with a diode laser for PeRCEAS vs. more voluminous Nd-YAG pumped dye laser setup). Its chain length is reported to be 150 ± 50 for standard pressure.…”
Section: Effective Chain Length Calibrationmentioning
confidence: 99%
“…A similar configuration using the PeRCA technique and a CRDS NO 2 detector (albeit without optical feedback) is described in Liu et al (2009), who reported on an instrument for ground-based measurements at standard pressure. It is a combination of a NO 2 CRDS detector (Hargrove et al, 2006) and a 5 m-long (Teflon) tubing system enabling the peroxy radical chemical conversion.…”
Section: Introductionmentioning
confidence: 99%
“…A knowledge of peroxy radical abundances and distributions is essential to determine the oxidising capacity of the lower atmosphere in general (Thompson, 1992) and to determine oxidation rates and hence transformations of primary pollutants on a variety of scales. In spite of their importance in the chemical processing of the troposphere, there are few measurement data available (Cantrell et al, 1992(Cantrell et al, , 1996Carpenter et al, 1997;Zanis et al, 1999;Burkert et al, 2001Burkert et al, , 2003Hanke et al, 2002;Handisides et al, 2003;Mihelcic et al, 2003;Green et al, 2003;Fleming et al, 2006aFleming et al, , 2006bKukui et al, 2008;Liu et al, 2009;Andres-Hernandez et al, 2001. The reported abundances of peroxy radicals during different field studies have large variability and apart from Electron Spin Resonance (ESR) type studies (e.g.…”
Section: Introductionmentioning
confidence: 99%